Parathyroid carcinoma: impact of preoperative diagnosis on the choice of surgical procedure - Yoshitaka Kawai; Yo Kishimoto; Hisanobu Tamaki; Takashi Fujiwara; Ryo Asato; Koji Ushiro; Shogo Shinohara; Shinpei Kada; Shinji Takebayashi; Tsuyoshi Kojima; Shuya Otsuki; Masakazu Miyazaki; et al. (Endocrine Journal)
The operative procedure in the surgical treatment of parathyroid carcinoma differs from that of benign hyperparathyroidism. However, preoperative differentiation is often difficult. This study elucidated how clinicians diagnose parathyroid carcinoma and the relationship between preoperative diagnosis and the operative course. Using a retrospective chart review, twenty cases of parathyroid carcinoma from nine participating centers were examined. In 11 cases with preoperative suspicion of malignancy, at least one of these three features was found: elevated serum calcium level (>14 mg/dL), palpable mass, and irregular margin on ultrasonography. Although an intact parathyroid hormone (iPTH) threshold to suspect malignancy has not been established, six cases showed marked iPTH elevation exceeding 8.0 times the upper limit of normal. One case was excluded from analysis due to hemodialysis. Compared with the four cases that showed calcium elevation, the iPTH threshold might represent better sensitivity. Among 9 cases of benign preoperative diagnosis, six cases were performed with pericapsular resection. In three cases where malignancy was suspected in the middle of the operation, the recommended en bloc resection with ipsilateral thyroid lobectomy was not performed but a parathyroidectomy with surrounding soft tissue. In contrast, 10 preoperatively suspected cases underwent en bloc resection, and one case underwent pericapsular resection followed by supplementary ipsilateral hemithyroidectomy due to the uncertain pre- and intraoperative findings to determine the diagnosis. In conclusion, the surgical procedure for parathyroid carcinoma strongly depends on the preoperative diagnosis. The presence of excessive iPTH levels might contribute to improved preoperative diagnostic sensitivity for parathyroid carcinoma.